No limits blow the cap off your capacity - Maxwell, John C. 1947- (Center Street, 2017)
We often treat the word capacity as if it were a natural law of limitation. Unfortunately, most of us are much more comfortable defining what we perceive as off limits rather than what's really possible. Could it be that many of us have failed to expand our potential because we have allowed what we perceive as capacity to define us? What if our limits are not really our limits? In his newest book, John Maxwell identifies 17 core capacities. Some of these are abilities we all already possess, such as energy, creativity and leadership. Others are aspects of our lives controlled by our choices, like our attitudes, character, and intentionality. Maxwell examines each of these capacities, and provides clear and actionable advice on how you can increase your potential in each. He will guide you on how to identify, grow, and apply your critical capacities. Once you've blown the "cap" off your capacities, you'll find yourself more successful--and fulfilled--in your daily life."--Amazon.com